Correlation of Oncotype DX Recurrence Score with the Expression of Insulin Receptor Substrate Proteins in Estrogen Receptor + Breast Cancer - Vighnesh Walavalkar; Jennifer L. Clark; Dina Kandil; Shaolei Lu; Kathryn Edmiston; Leslie M. Shaw; Ashraf Khan (Journal of Cancer Genetics And Biomarkers, 2014)
Insulin receptor substrate (IRS) 1 and 2 are downstream signaling proteins that influence breast pathophysiology. IRS-1 promotes carcinoma cell proliferation; whereas IRS-2 regulates cell motility, invasion, and glycolysis. Our lab has shown that distinct cellular localization of IRS-2 also plays a role in carcinoma cell function. Oncotype DX (Genomic Health) (ODX) is a 21-gene expression profile used to classify carcinomas with low, intermediate, and high risk recurrence scores (RS). Our aim is to correlate expression and cellular localization of IRS proteins in breast carcinomas with their ODX RS. 97 breast carcinomas sent for ODX testing from 2006-2009 were collected and grouped according to their RS (low, intermediate or high). Immunohistochemistry for IRS-1/-2 was performed. Specific criteria were used to evaluate IRS staining patterns. Follow-up data, ranging from 3-6 years, was available. Statistical analysis was performed to correlate staining patterns of IRS-1/-2 with the three RS groups. IRS-1 staining, predominantly nuclear, did not significantly correlate with RS (P=.5645). IRS-2 expression patterns did show statistical significance amongst the three RS groups (P=.0371). Tumors with intermediate and low RS were more likely to exhibit punctate and diffuse cytoplasmic expression of IRS-2, and cell membrane expression was uncommon in this group. Expression and cellular localization of IRS proteins play an important role in breast cancer cell biology, and expression patterns for IRS-2 do demonstrate a significant correlation with ODX RS. Further studies are required to elucidate the significance of cellular localization of IRS-1/-2 proteins in breast carcinoma cells and their relationship to ODX scores.
Keywords: breast cancer